Training and burn care in rural India - Shobha Chamania (Indian Journal of Plastic Surgery)
Burn care is a huge challenge in India, having the highest female mortality globally due to flame burns. Burns can happen anywhere, but are more common in the rural region, affecting the poor. Most common cause is flame burns, the culprit being kerosene and flammable flowing garments worn by the women. The infrastructure of healthcare network is good but there is a severe resource crunch. In order to bring a positive change, there will have to be more trained personnel willing to work in the rural areas. Strategies for prevention and training of burn team are discussed along with suggestions on making the career package attractive and satisfying. This will positively translate into improved outcomes in the burns managed in the rural region and quick transfer to appropriate facility for those requiring specialised attention.